A configuração da docência no ginásio do Espírito Santo (1906-1951) - Borel, Tatiana (2017)
It analyzes the configuration of teaching in the Espírito Santo Gymnasium / State School in the first decades of the XX century (1906-1951). The temporal cut is marked by the creation of the Espírito Santo Gymnasium in 1906, and the foundation of the Philosophy, Sciences and Letras College of Espírito Santo (FAFI) in 1951. It aims to investigate the formative and professional paths of teachers who taught in the main Capixaba institution of secondary education, prioritizing glances for rituals that involved the starting point, the teaching conceptions, as well as traces of the practices that endured within the passing of time. It describes a historical overview regarding the gymnasium as a public secondary education institution in Espírito Santo, evidencing aspects of its creation and functioning. Amongst them, the alternation of administration between State and Church; the various addresses that housed the gymnasium; the salaries earned by teachers; open exams for professors; the teaching practices undertaken; the notoriety among the capixaba society; and intellectual production inside and outside the school space. In order to do so, it uses as sources: reports of inspectors and presidents of the State; newspaper clippings (various); official documents about the creation and operation of the GES (Espirito Santo Gymnasium); minutes of the Congregation and minutes and reports of open exams; legislation; various magazines, including Vida Capichaba and Revista Comandos; crafts; documents of assimilation with Colégio Pedro II; personal documents such as letters and photographs; as well as testimonies collected in an interview. The analysis dialogues with the theoretical contributions of the historians Marc Bloch (2001) and Carlo Ginzburg (2002). It values the importance of historical testimonies, the understanding of diversity and the tangling of sources. It was sought to narrow the scale of analysis to enable details to surface. The available sources were interrogated with the intention of making them speak. The final discussions indicate that, despite having suffered structural difficulties, the Gymnasium of Espírito Santo has never ceased to develop its activities, reaching the process of equating to Pedro II College, on two occasions. As far as professors were concerned, they were, for the most part, people who had a certain popularity and who had no education in the area of education, and who were, therefore, involved in other spheres of society. As for the entering of the teachers in the GES, political interference in the admission and / or permanence processes of the professors were frequent. It was also verified that, although it followed a specific regiment, the teaching practices were developed from particularities of the teachers, who engendered personal interests and affinities in the way of teaching in the Gymnasium of Espirito Santo / State School.